Bortezomib and fenretinide induce synergistic cytotoxicity in mantle cell lymphoma through apoptosis, cell-cycle dysregulation, and IκBα kinase downregulation. Issue 9 (October 2015) - Cowan, Andrew J.; Frayo, Shani L.; Press, Oliver W.; Palanca-Wessels, Maria C.; Pagel, John M.; Green, Damian J.; Gopal, Ajay K.
Abstract : Mantle cell lymphoma (MCL) remains incurable for most patients, and proteasome inhibitors like bortezomib induce responses in a minority of patients with relapsed disease. Fenretinide is a retinoid that has shown preclinical activity in B-cell lymphomas. We hypothesized that these agents could yield augmented antitumor activity. MCL lines (Granta-519, Jeko-1, and Rec-1) were treated with escalating concentrations of bortezomib and fenretinide singly and in combination. Cytotoxicity was assessed using the MTT assay. Flow cytometric methods were used to assess apoptosis and necrosis, with annexin V-FITC/propidium iodide staining, and G1 and G2 cell-cycle changes were assessed by DAPI staining. Changes in cyclin D1, cyclin B, IκBα, and IKKα expressions were quantified by western blotting. Cytotoxicity was mediated through apoptosis; both agents showed observed versus expected cytotoxicities of 92.2 versus 55.1% in Granta-519, of 87.6 versus 36.3% in Jeko-1, and of 63.2 versus 29.8% in Rec-1. Isobolographic analysis confirmed synergy in Jeko-1 and Rec-1 cell lines. Bortezomib induced G2-phase arrest, with a 1.7-fold increase compared with control, and fenretinide resulted in G1-phase arrest, with an increase of 1.3-fold compared with control. In the combination, G2-phase arrest predominated, with a 1.4-fold increase compared with control, and there was reduced expression of cyclin D1 to 24%, cyclin B to 52 and 64%, cyclin D3 to 25 and 43%, IκBα to 23 and 46%, and IκBα kinase to 34 and 44%. Bortezomib and fenretinide exhibit synergistic cytotoxicity against MCL cell lines. This activity is mediated by IκBα kinase modulation, decreased cyclin expression, cell cycle dysregulation, and apoptotic cell death.